Asprosin infusion modulates central circuits to rescue selective serotonin reuptake inhibitor-induced male dysfunction - Tan, Fatih; Oz, Zeynep Dila; Zorlu, Gokhan; Erdogan, Cihan Suleyman; Ozdede, Mehmet Ridvan; Kacar, Emine; Kelestimur, Haluk (Oxford Univ Press, 2026)
In brief Antidepressant-induced sexual dysfunction and infertility are major clinical challenges that lack effective pathophysiological solutions. We show that the fasting-induced adipokine asprosin acts centrally to restore erectile function, copulatory behavior, and testicular morphology in selective serotonin reuptake inhibitor-treated rats, positioning it as a promising therapeutic candidate. Selective serotonin reuptake inhibitors (SSRIs) are one of the most commonly prescribed drugs worldwide and sexual dysfunction is one of the most common side effects of SSRI use. As a fasting-induced adipokine that crosses the blood-brain barrier to activate orexigenic agouti-related peptide neurons, asprosin may link energy homeostasis to the hypothalamic-pituitary-gonadal axis; thus, we investigated its potential to modulate sexual activity and mitigate SSRI-induced reproductive impairment, given that SSRIs disrupt metabolic signaling to exacerbate sexual dysfunction. A total of 60 male Sprague-Dawley rats were randomized into control, sham, paroxetine (20 mg/kg/day via oral gavage), asprosin (500 ng/kg/day via intracerebroventricular infusion), and paroxetine + asprosin groups (n = 12/group). Following behavioral assessments, we analyzed serum hormones, sperm parameters, and reproductive histology, alongside hypothalamic Kiss1 and Rfrp-3 expression within the arcuate nucleus of hypothalamus, dorsomedial hypothalamus, and rostral periventricular area of the third ventricle, with statistical significance set at p < 0.05. Asprosin enhanced erectile responses, facilitated ejaculation, and increased sexual motivation. Paroxetine-induced testicular damage, characterized by interstitial edema, vascular congestion, and detachment of the seminiferous tubule basement membrane, was ameliorated by asprosin. Paroxetine reduced sperm concentration versus controls, whereas asprosin increased sperm concentration relative to both control and paroxetine groups. Total sperm motility decreased in the paroxetine group and was restored by asprosin. Asprosin decreased prolactin levels and increased oxytocin levels. Rfrp-3 and Kiss1 mRNA levels were not altered by paroxetine, while it counteracted the asprosin-induced elevations in the arcuate nucleus of hypothalamus and dorsomedial hypothalamus. Our findings indicate that asprosin exerts pro-fertility effects and modulates central reproductive circuits, suggesting that asprosin is a key regulator of metabolic status and male reproduction.
Keywords: asprosin; sexual behavior; reproductive system; sexual dysfunction; SSRI; sperm